Sistem Pendukung Keputusan Kelompok untuk Menentukan Penerima Bantuan Kemiskinan di Kota Malang Menggunakan Metode PROMETHEE II dengan Copeland Score - Ridwan Fajar Widodo; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malang City is one of the most populous cities in Indonesia. Poverty data collection is often a problem in determining poverty support beneficiaries, and some of the problems arising from poverty data collection are not found for residents without E-KTP, human resources are not eligible, and the data collection process is still done manually using paper, which requires a longer selection time. The PROMETHEE II method, Weighted Product, and Simple Additive Weighting are used in decision making by decision-makers. The system test is made by providing different criteria for each variable and indicator, and five tests were performed to measure the accuracy of the system, and the test results obtained 4 tests that obtained 100% results for each variable. The family variable in the second test tube can reach 20% and for the individual variable, it can reach 60Â° in the third data test. The level of accuracy obtained as a result of these tests is that the differences in the distribution data used are not evenly distributed. This will cause the level of accuracy obtained to fluctuate based on the data for each reference weight. Testers, the level of accuracy of the site can explain the results more accurately.